2020
DOI: 10.1186/s12955-020-01347-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment instruments for adults: a systematic review of population-based studies

Abstract: Background: Against a backdrop of population aging and improving survival rates for chronic noncommunicable diseases (CNCD), researchers are placing growing emphasis on health-related quality of life (HRQoL). The aim of this study was to identify the QoL assessment instruments used in population-based studies with adults conducted around the world. Methods: A systematic review of original research published in all languages between 2008 and 2018 was conducted. Systematic reviews and meta-analyses were excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 78 publications
1
123
1
13
Order By: Relevance
“…Based on the above, an assessment that is capable of capturing the dynamic interaction between the individuals' external living conditions and their internal perception of these conditions has been progressively claimed [14,15]. This is one of the main reasons why measuring individuals' quality of life (QOL) is becoming increasingly popular, with the aim of capturing individuals' perception of their own health and their hopes, expectations and feelings after the delivery of health care [12,16]. Additionally, QOL assessment has also been considered an important outcome of healthcare delivering in different clinical scenarios [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, an assessment that is capable of capturing the dynamic interaction between the individuals' external living conditions and their internal perception of these conditions has been progressively claimed [14,15]. This is one of the main reasons why measuring individuals' quality of life (QOL) is becoming increasingly popular, with the aim of capturing individuals' perception of their own health and their hopes, expectations and feelings after the delivery of health care [12,16]. Additionally, QOL assessment has also been considered an important outcome of healthcare delivering in different clinical scenarios [17].…”
Section: Introductionmentioning
confidence: 99%
“…Still, the adequate selection of the evaluation instruments is of remarkable recognition and value, preferably those speci c to the context under analysis, as these can produce results that are closer and more reliable to the reality under study (23). On this subject, the present review showed that, despite the majority of studies using speci c HRQoL questionnaires for PD, some researchers choose general assessment instruments.…”
Section: Discussionmentioning
confidence: 91%
“…The second category analyses factors resulting from the disease itself (disease-speci c). This category is important because of its ability to assess the patient's well-being, the severity of symptoms, the impact of the disease on both emotional state and daily -social and occupational -activities [29]. There are numerous questionnaires available for measuring OHRQoL, however, the most frequently used questionnaires include Geriatric Oral Health Assessment Index (GOHAI) and Oral Health Impact Pro le (OHIP) containing 49 or 14 items (OHIP-49, OHIP-14).…”
Section: Discussionmentioning
confidence: 99%